Association mapping to exploit maize diversity for drought tolerance: landraces and early testcrosses as genetic resources - Barbosa, Pedro Augusto Medeiros (2020)
Maize (Zea mayz L.) production worldwide have been facing a tremendous obstacle in the past years, drought events are increasing in frequency and severity, mainly in tropical and subtropical regions. Moreover, climate change forecasts this as a trend for the next few years as well. The maize production can be highly affected by water deficiency stress, resulting in losses in grain yield. Mexico is the center of origin of maize, and there are many diversity centers across Latin America. This diversity should be exploited by breeding programs once it is a source of new alleles that can be responsible for the needed genetic improvements to face the forecasting challenges. This doctoral thesis addresses the theme in two sections. First, we present a review of maize genetic diversity, the use of landraces introduction in breeding programs to improve for drought tolerance, highlighting the importance to develop improved tropical germplasm to face the drought issue. In this review we also discuss the opportunity to apply Genome-Wide Associations Studies (GWAS) and Marker-Assisted Selection (MAS) in this context. In the second section we present an original GWAS application in a pre-breeding program using selected landraces as genetic sources for drought tolerance maize improvement. The aim was to tudy the genetic resources of a landrace panel to identify maize chromosomal regions associated with drought tolerance. For that, we performed the GWAS in 1306 landraces progenies originated from 20 landraces populations selected due to its agricultural performance in dry regions of Latin America. Phenotypic data were obtained from early testcross trials of two generations (BC1S1 in 2016 and BCS2 in 2017) conducted in two water regimes, irrigated and drought condition, in three locations in Mexico. Harmonic Mean of Relative Performance (HMRP) of grain yield in both water regimes was used as a measure of drought tolerance of the genotypes. The genotypic values were estimated using a spatial adjustment in a two-stage analysis. A final set of 5,695 single-nucleotide polymorphism (SNPs) markers was considered for GWAS. We were able to detect a total of 10 significant markers associated with grain yield and drought tolerance index, and we suggest two putative genes mapped close to two of these markers that can be part of the plant\'s response to drought stress. Besides, for two associated SNPs, the alleles from landraces provided a slightly higher yield under drought conditions. Our results indicate that the diversity delivered by these landraces combined with commercial lines is an exciting strategy to improve maize for drought tolerance.